PELATIHAN TARI KREASI MINANGKABAU PADA PENGEMBANGAN DIRI DI SMK KARTIKA 1-2 PADANG - Olivia Dwi Saljuni; Yuliasma (Universitas Negeri Padang, 2025)
This study aims to determine and describe creative dance training on self-development at SMK Kartika 1-2 Padang. The type of research in this study is qualitative with descriptive methods. This research was conducted at SMK Kartika 1-2 Padang and the objects in this study were students who participated in dance self-development at SMK Kartika 1-2 Padang. The research instrument was the researcher himself, then assisted by a laptop, camera and stationery. Data collection techniques used in this study were observation and interviews and data analysis techniques used in this study were data reduction, data presentation, and drawing conclusions. The results of this study explain that creative dance training at SMK Kartika 1-2 Padang by preparing creative dance materials that are appropriate to students' needs, varied properties are able to form discipline, cooperation, and appreciation of students through self-development at SMK Kartika 1-2 Padang.